The effect of atropine used in dobutamine stress echocardiography on pupil diameter. Issue 6 (November 2022) - Soulis, Dimitrios; Papaioannou, Theodore G; Zozolou, Maria; Daskalopoulou, Stella; Vlachopoulos, Charalampos; Bethanis, Dimitrios; Triantafyllou, Dimitrios
Background: The use of atropine during dobutamine stress echocardiography (DSE) is contraindicated in persons with narrow angle glaucoma though there is limited evidence that low doses of intravenous atropine do not cause pupillary dilation. Objective: The aim of this study is to investigate whether atropine when administered in persons without glaucoma during dobutamine stress echocardiography causes pupillary dilation. Methods and Results: Out of 144 patients without a history of glaucoma referred for DSE for clinical indications, 105 patients received intravenous atropine doses ranging from 0.1 mg to 1.25 mg (most patients received 0.25–0.75 mg). Pupil diameter of both eyes was measured under the same light conditions before and after the DSE using a CP-30 Optical Digital PD Ruler. For the total of 210 examined eyes pupil diameter remained unaltered after each DSE test (3.65 ± 0.799 mm before vs 3.63 ± 0.766 mm after, p = .737). Similarly, pupil diameter remained unchanged when left and right eyes were assessed separately (right eye: 3.770 ± 0.812 before vs 3.752 ± 0.745 mm after, p = .821 and left eye: 3.521 ± 0.770 before vs 3.499 ± 0.770 mm after, p = .806). Diameter of right and left pupil were also unaltered after grouping patients by sex and iris pigmentation. Age, weight, atropine dose and propranolol dose were not correlated with changes in pupil diameter. Conclusion: Intravenous atropine in usual doses administered in DSE does not cause mydriasis in adults without glaucoma. Future studies need to confirm our findings and expand the investigation regarding safety of atropine use during DSE in patients with narrow angle glaucoma.